University Governance in the Context of Vietnam’s Educational Innovation (Journal of Contemporary Educational Policies and Practices, 2021)
University governance brings about the success of a university. Renovation of management in the direction of university governance will exert important influences to improve the training quality of the higher education system. The article presents the theoretical basis and research process related to university governance activities to promote education innovation. The study combined qualitative and quantitative research; the survey sample was 120 people, of which 44 were managers and 76 were lecturers and staff working at Saigon University. The article proposes university governance related to such elements as planning for the development of resources in the university, policy mechanisms, organization and leadership, and monitoring. The article clarifies the relationship between the components of university governance activities in the direction of a system approach to help universities manage their activities towards sustainable university governance.